Rafflesia patma (RAFFLESIACEAE): NOTES ON ITS FIELD STUDY, CULTIVATION, SEED GERMINATION AND ANATOMY - Mursidawati, Sofi; Irawati, Irawati; Ngatari, Ngatari (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2014)
Rafflesia spp. (Rafflesiaceae) have a strategic value from both scientific and conservation viewpoints. To date only very few attempts have succeeded in growing the species ex situ and the main protection measures have been by in situ conservation. More detailed studies are required to understand the relationships between Rafflesia spp. and their host plants in order to improve their management and conservation. Studies on the anatomy, in vitro culture and seed germination in connection with conservation have been conducted in the Bogor Botanic Gardens. Effort to transfer Rafflesia patma to an ex situ conservation area has produced some flowers. However, we encountered a bigger challenge to maintain the long term presence of R. patma in ex situ conservation, since a high number of individuals is required to make the viable population.